Simulation of Diffusion Mechanism and Dynamics in Alumina Liquid under Pressure - Ha, Nguyen Thi Thanh; Hung, Pham Khac (VNU Journal of Science: Mathematics - Physics, 2013)
Abtract: Diffusion mechanism and dynamics in Al 2 O 3 liquidhave been studied via molecular dynamics simulation. Six models with different density and at temperature of 3000 K have been used to study the atomistic mechanism governing the process of the bond-breaking and bond-reformation (the transition AlO x ® AlO x+1 and AlO x ® AlO x-1 ). Calculation shows that the diffusion of particle Al is realized via the transition AlO x ® AlO x ± 1 and the rate of transition AlO x ® AlO x ± 1 monotonously increases with pressure.  When applying pressure to liquid the diffusion mechanism changes from strong localization of transitions SiO x ® SiO x ± 1 in the sample at ambient pressure to uniform distribution transitions SiO x ® SiO x ± 1 in high-pressure sample. Furthermore, we find two distinguish regions with quite different coordination environment where the rate of transitions SiO x ® SiO x ± 1 strongly differs from each other. The result obtained clearly evidences the spatially heterogeneous dynamics in the liquid.